History and Dynamics of Madrasas in Indonesia - Annisa Urrobingah; Apri Akmal Muzaky; Mei Fajri Rahayu; Fahri Hidayat (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
Madrasa etymologically is Darosa which means a place where the learning process occurs. Whereas in terms of terminology, madrassas are devoted to Islamic institutions or under the auspices of the Ministry of Religion. Madrasas began to develop since the 20th century. During its development of Islam in the world, madrassas were directed at higher education institutions during pre-modern times. Currently Madrasas in Indonesia have three levels, where the lowest level is Madrasah Ibtida'iyah (MI) which is equivalent to Elementary Schools (SD), Madrasah Tsanawiyah (MTs) equivalent to Junior High Schools (SMP), and Madrasah Aliyah (MA ) equivalent to high school (high school). In Indonesia the term madrasa is not very well known at first. Initially Islamic education in Indonesia was carried out in pesantren, tajug, surau, langgar, mosque. The purpose of this study is to find out the history and development of madrasas in Indonesia.